2021
DOI: 10.3390/brainsci11070830
|View full text |Cite
|
Sign up to set email alerts
|

How Visual Word Decoding and Context-Driven Auditory Semantic Integration Contribute to Reading Comprehension: A Test of Additive vs. Multiplicative Models

Abstract: Theories of reading comprehension emphasize decoding and listening comprehension as two essential components. The current study aimed to investigate how Chinese character decoding and context-driven auditory semantic integration contribute to reading comprehension in Chinese middle school students. Seventy-five middle school students were tested. Context-driven auditory semantic integration was assessed with speech-in-noise tests in which the fundamental frequency (F0) contours of spoken sentences were either … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…However, with the development of early reading education activities by educators in some Asian countries, the problem of children's dyslexia had gradually attracted the attention of researchers. Therefore, it was not surprising that Asian countries (China, Japan, and Israel) had their language as one of their research focuses (104,(121)(122)(123)(124)(125)(126)(127)(128).…”
Section: An Analysis Of Author Abstract From a Country Perspectivementioning
confidence: 99%
“…However, with the development of early reading education activities by educators in some Asian countries, the problem of children's dyslexia had gradually attracted the attention of researchers. Therefore, it was not surprising that Asian countries (China, Japan, and Israel) had their language as one of their research focuses (104,(121)(122)(123)(124)(125)(126)(127)(128).…”
Section: An Analysis Of Author Abstract From a Country Perspectivementioning
confidence: 99%
“…This hypothesis was first confirmed in Hoover and Gough (1990) where the product of decoding and listening comprehension significantly accounted for an extra 1%–7% of variances in English reading comprehension in Grades 1–4 with Spanish speakers learning to read English. However, subsequent studies from alphabetic languages (e.g., Neuhaus et al, 2006 ; Conners, 2009 ; Georgiou et al, 2009 ) and Chinese ( Li et al, 2021 ) failed to replicate such finding. Hoover and Tunmer (2018) explained that “testing such a difference (between additive and multiplicative model) requires a special population where skills are nonexistent for a substantial number of children in at least one of the components” (p309).…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, Joshi et al (2012) found that the importance of decoding increased from Grade 2 to Grade 4. A recent study even found that the role of decoding can last until middle school ( Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies focused on the relationship between decoding and reading comprehension, particularly in alphabetic languages (e.g., Jenkins et al, 2003 ; Rasinski et al, 2005 ; Yovanoff et al, 2005 ; Klauda and Guthrie, 2008 ). There are, however, some studies on (non-alphabetic) Chinese reading comprehension that examined character recognition and comprehension (e.g., Joshi et al, 2012 ; Yeung et al, 2016 ; Li et al, 2021 ). For example, Joshi et al (2012) found that the SVR as incorporated in the componential model of reading (CMR) is also applicable to Chinese other than English.…”
Section: Introductionmentioning
confidence: 99%
“… Yeung et al (2016) examined the interrelationships between linguistic comprehension skills, decoding and reading comprehension within Chinese children in a longitudinal study, and found that linguistic comprehension and decoding were the main predictors for a significant amount of variance in sentence and passage comprehension. Similarly, Li et al (2021) examined how Chinese character decoding and context-driven auditory semantic integration contributed to reading comprehension among Chinese middle school students by administering speech-in-noise tests, and found that performance in Chinese character decoding and auditory semantic integration scores with the flattened (but not natural) fundamental frequency contours of spoken sentences significantly predicted reading comprehension.…”
Section: Introductionmentioning
confidence: 99%